Psikoedukasi: Stop Kekerasan Seksual pada Anak, kepada Guru dan Orang Tua di Majelis Taklim Elhamidy Bakalan Beji Pasuruan - Nazlah Hasni; Alifia Rahma; Iswinarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Majelis Taklim Elhamidy is a religious educational institution located in Kelurahan Pagak, Beji District, Pasuruan Regency, East Java. The teachers and parents at this institution have never received counseling on the prevention of sexual violence against children. This knowledge is very important, especially considering that recently, child sexual abuse and violence can occur anywhere and at any time. The psychoeducation program